(untitled) (TAMADDUN NURI JURNALI, 2025)
This article examines the processes of borrowing Anglicisms in professional and media discourses of the modern Russian language. It analyzes the factors contributing to the active penetration of English loanwords, their adaptation, and functioning in various communicative spheres. Special attention is paid to lexicographic challenges associated with the inclusion of borrowings in dictionaries, as well as prospects for their systematization. The study is based on an analysis of current linguistic sources and lexicographic practices.